Comparison of trace metal concentrations in malign and benign human prostate - Yaman, M; Atici, D; Bakirdere, S; Akdeniz, I (Amer Chemical Soc, 2005)
Imbalance in the composition of trace metals, recognized to be essential to normal human homeostasis, besides the accumulation of potentially toxic or nonessential trace metals, may cause disease. Thus, there is a need for their analysis in cancerous and noncancerous human tissues to examine the relationship between cancer and these elements. Trace metal concentrations including Cd, Ni, Zn, Cu, Fe, Mg, and Ca in both malign and benign prostate samples were determined by atomic absorption spectrophotometry. The tissues were digested by using microwave energy. In contrast to the literature data for zinc, the concentrations of calcium and zinc in the malign human prostate were found to be significantly higher than those in the benign human prostate (p < 0.05 for both metals). Similarly, the concentrations of iron, nickel, and magnesium in the malign prostate were also found to be higher than those in the benign prostate (p less than or equal to 0.1). Therefore, it is understood that more studies are needed regarding the increase or decrease in the metal (particularly Ca and Zn) concentrations of malign prostate samples.
Keywords: Zinc; Cadmium; Carcinogenesis; Citrate; Copper